Bariatric surgery in older adults: Should there be an age limit?. Issue 3 (January 2019) - Susmallian, Sergio; Raziel, Asnat; Barnea, Royi; Paran, Haim
Abstract : Abstract: Obesity has become one of the most significant health problems worldwide, affecting more than one-third of the global population. The elderly population is not immune to this proportional increase in obesity. To date, there is no cure for obesity, but surgery is the most effective treatment available today. We analyzed the results of bariatric surgery in elderly patients for a period of 3 years. Patients 65 years old and older were included in the study, 451 older adults were included. The mean age of the study group was 67.92 years old (min. 65, max. 84). The mean body mass index (BMI) was 40.32 Kg/m 2 (min. 34 and max. 59). Sleeve gastrectomy (SG) was the most common procedures, and were conducted in 346 (76.72%) patients, gastric bypasses (GBPs) in 53 (11.75%) of which 33 were roux en y GBP (7.32%) and 20 mini GBPs (4.43%), gastric banding in 48 (10.64%), and duodenal switching in 4 (0.89%) cases. There were 40 (8.86%) patients with perioperative complications, 6 (1.33%) required re-operations, 12 (2.66) patients with operative complications were treated conservatively, 8 (1.77%) re-admission 5 of them with intrabdominal abscess, and 14 (3.10%) with co-morbidities complications. More than 76% of the patients had co-morbidities, 1 year after surgery the average remission of diseases was 34.74%, the improvement was49.67% and no changes in the co-morbidities was 15.59%. There were no deaths reported in this cohort. The mean excess body weight (EBW) loss among the patients was 70.76% (from 32% to 92%). No failure of weight loss (less than 25% of EBW loss) was observed after the first postoperative year. Bariatric surgery offers obese elderly patients an acceptable result, and it can be offered to improve the quality of life of these patients. A new consensus conference panel is needed to set appropriate recommendations regarding criteria that limit bariatric surgery in older adults.